Technology Capability Perception & Sustaining Competitive Advantage Challenge for Private Higher Institution: a Review of Literature - Hussain, Suhaidah; Mad Lazim, Halim; Azlan Taib, Che (International Journal of Engineering and Technology, 2018)
Private Institution of Higher Education Institutions (PvIHEs) in Malaysia is facing stiff competition from local and international institutions that offers various programmes.Â The sustainability of PvIHEs is highly depending on several factors such as programmes offered, teaching and learning facilities, location, conducive environment, teaching staff and etc.Â The focus of this paper was to review the literature review of sustaining competitive advantage factors for PvIHEs.Â Furthermore in order to discover the technology capability perception of people on sustaining competitive advantage, an application of Theory of Planned Behaviour is applied.Â The Theory of Planned Behaviour was used by various researchers in various setting.Â The literature review of this study discloses the previous scholar on the related areas in sustaining competitive advantage, Theory of Planned Behavior and the perception of technology capability of a private higher education institution.Â